2007
DOI: 10.1002/cncr.22858
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer laterality as a rationale of focal ablative therapy for the treatment of clinically localized prostate cancer

Abstract: BACKGROUND.Early detection of small-volume prostate cancer (PCa) has led to the concept of focal therapy to treat PCa as an organ-sparing, minimally invasive procedure. The authors sought to determine the frequency of unilateral cancers in the contemporary prostate-specific antigen (PSA) era to determine the percentage of patients who would be candidates for hemiablation of the prostate by using focal therapy while preserving the contralateral lobe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(70 citation statements)
references
References 14 publications
1
64
1
4
Order By: Relevance
“…23 Out of 261 men with low-risk prostate cancer, defined as clinical stage T1c or T2a, PSA <10 ng/mL, Gleason score ≤6 and only 1 or 2 ipsilateral positive cores on at least sextant biopsy, only 93 (35.1%) had unilateral disease following examination of radical prostatectomy specimens. Coming from the opposite perspective, the authors of another analysis of 1184 radical prostatectomy specimens have reported that 1 out of 5 patients had unilateral, small volume prostate cancer that could be treated with FT. 5 Our analysis revealed that only 45 (28%) out of 161 studied patients with preoperative unilateral prostate cancer, based on biopsy findings, had unilateral disease after radical prostatectomy specimens evaluation. These results confirm that, by using current biopsy schemes, only a small percentage of patients can be correctly identified with unilateral prostate cancer; other preoperative parameters are mandatory for better patients' selection.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…23 Out of 261 men with low-risk prostate cancer, defined as clinical stage T1c or T2a, PSA <10 ng/mL, Gleason score ≤6 and only 1 or 2 ipsilateral positive cores on at least sextant biopsy, only 93 (35.1%) had unilateral disease following examination of radical prostatectomy specimens. Coming from the opposite perspective, the authors of another analysis of 1184 radical prostatectomy specimens have reported that 1 out of 5 patients had unilateral, small volume prostate cancer that could be treated with FT. 5 Our analysis revealed that only 45 (28%) out of 161 studied patients with preoperative unilateral prostate cancer, based on biopsy findings, had unilateral disease after radical prostatectomy specimens evaluation. These results confirm that, by using current biopsy schemes, only a small percentage of patients can be correctly identified with unilateral prostate cancer; other preoperative parameters are mandatory for better patients' selection.…”
Section: Discussionmentioning
confidence: 78%
“…Even though prostate cancer is known as a multifocal disease, contemporary studies report an increase in frequency of cancer unifocality from 13% to 38% and unilaterality from 19% to 63%. [3][4][5] Focal therapy has gained a place in the group of potential prostate cancer treatment modalities and several studies are working on the efficacy and reliability of this therapeutic option. Focal therapy may provide sufficient oncological results and minimize postoperative morbidity, although long-term cancer specific survival data are missing.…”
mentioning
confidence: 99%
“…Recent studies have suggested that only a very small minority of men undergoing radical prostatectomy have pathologically unilateral disease with low risk features that may be amenable to hemiablation of the prostate. 8,23 However, neither of these groups evaluated the proportion of patients with bilateral disease with clinically insignificant tumour foci (o0.5 cm 3 tumour volume, Gleason score p6) on the side contralateral to the index lesion. Role of prostate cancer focality in focal therapy M Karavitakis et al…”
Section: Discussionmentioning
confidence: 99%
“…3 The principal theoretical objection to focal prostate therapy includes the multifocal nature of PCa. However, recent histological studies within the PSAscreening era from the United States have shown that in men undergoing radical prostatectomy, 10-40% have unilateral disease [4][5][6][7][8] and 10-44% have unifocal tumours. [9][10][11][12] These data raise the possibility that halfgland treatment (hemiablation) or focal ablation of tumour foci alone might be possible for between 10% and up to 50% of patients who would currently receive whole-gland treatment; on average, about one-third of men would be suitable.…”
Section: Introductionmentioning
confidence: 99%
“…Age, PSA, pathological Gleason score, lymph node status, seminal vesicle invasion, extracapsular extension, positive surgical margin status, year of surgery, race, adjuvant XRT, percent tumor involvement in the RP specimen (measured as described previously 5 ) and prostate weight were evaluated as possible predictors of BCR in multivariate Cox regression analysis. As PSA and prostate weight had a non-normal distribution and a nonlinear effect of these variables was expected, these variables were transformed to the natural logarithm before analysis.…”
Section: Discussionmentioning
confidence: 99%